A church of passion and hope : the formation of ecclesial disposition from Ignatius Loyola to Pope Francis and the new evangelization /: the formation of ecclesial disposition from Ignatius Loyola to Pope Francis and the new evangelization. (2016) - Goulding, Gill
No abstract available